Evaluasi Kualitas Sistem Informasi Kepegawaian di BKPSDM Kota Salatiga Berdasarkan ISO/IEC 25010 - Cindi Tiffany Wahyono Putri; Johan J.C Tambotoh J.C Tambotoh (STMIK Banjarbaru, 2025)
The Personnel Management Information System (SIMPEG) is an important component in supporting the management of personnel data, especially in government environments. This research aims to evaluate the quality of SIMPEG used by BKPSDM Salatiga City by referring to the international standard ISO/IEC 25010. This standard covers eight main aspects in assessing software quality, namely: Functional Suitability, Performance efficiency, compatibility, Usability, Reliability, Security, Maintainability, and Portability. The research method used is a quantitative survey by distributing questionnaires to 25 employees who actively use the system. The evaluation results show that SIMPEG Salatiga is in the